PAPR Reduction in MIMO-OFDM Using Modified PTS Scheme With Hybride ABC-FF Algorithem - Aruna Kumari, K.; K. Sri Rama Krishna, Dr. (International Journal of Engineering and Technology, 2018)
Orthogonal Frequency Division Multiplexing (OFDM) is an admired method for high data rate wireless transmission. OFDM can be clubbed with antenna arrays at the transmitter and receiver to increase diversity gain to enhance the system capacity on time variant and frequency selective channels, resulting in (Multi input and Multi output)MIMO. One main flaw of MIMO-OFDM is that the signals transmitted on different antennas might exhibit a prohibitively large Peak-to-Average Power Ratio (PAPR). There are two techniques mainly used to mitigate the effect of PAPR namely Partial Transmit Sequence (PTS) and Selective Mapping (SLM). In this paper a new optimized Partial Transmit Sequence (PTS) scheme and SLM for PAPR reduction in MIMO-OFDM have been proposed. Both the techniques are connected in series to get efficient throughput. Hybrid of ABCâ€“FF algorithm has been intended for optimal phase factor. The proposed technique has achieved better results than existing techniques. This intended technique has been implemented on the working platform of MATLAB.Â Â